Outcomes and cost-effectiveness of an integrated holistic care package on persons affected by podoconiosis, lymphatic filariasis and leprosy and community members in north-western Ethiopia: an implementation research study - Oumer Ali; Awoke Mihretu; Natalia Hounsome; Vasso Anagnostopoulou; Stephen A. Bremner; Mersha Kinfe; Asrat Mengiste; Maya Semrau; Abebaw Fekadu; Gail Davey (BMC Medicine)
Abstract Background Most studies on integration of neglected tropical disease programmes have focused on mass drug administration or environmental measures rather than Disease Management, Disability and Inclusion (DMDI). The study reported here explored integration of a DMDI care package across three disabling, stigmatising neglected tropical diseases (podoconiosis, lymphatic filariasis and leprosy), across physical and mental health, and into the state health system. Methods We conducted this pre-post study, the third phase of an implementation research project, in two predominantly rural districts in north-west Ethiopia in 2021. We assessed physical and mental health outcomes on 192 affected persons and 817 community members at baseline and 6 months after initiation of the integrated care package, implemented by nurses and health officers. Key outcomes measured were disability (using WHODAS-2.0), depression (Patient Health Questionnaire-9), discrimination (Discrimination and Stigma Scale), internalised stigma (Internalized Stigma Related to Lymphoedema), quality of life (Dermatology Life Quality Index) and social support (Oslo-3 Social Support Scale). Mixed effects linear regression models were used to estimate change in outcomes between baseline and 6 months after initiation of the care package. We also evaluated implementation feasibility and conducted cost-effectiveness analysis. Results Among 221 patients, improvements were observed in foot (− 2.3 cm; 95% CI: − 2.2, − 1.8) and leg circumference (− 1.8 cm; − 2.0, − 1.7) and acute attacks (6.2; 0.0, 6.6); these were statistically significant at the 5% level. Reductions were seen in disability scores (− 6.5; − 7.6, − 5.5), depression (− 5.3; − 6.6, − 4.6), discrimination (− 3.3; − 4.2, − 2.3), internalised stigma (− 3.7; − 4.6, − 2.8), quality of life (− 4.0; − 4.8, − 3.2), and alcohol use (− 1.6; − 2.4, − 0.8). No notable changes were found in the presence of wounds or moss, or perceived social support. Across 817 community members, there was strong evidence that knowledge improved, and stigmatising attitudes and social distance reduced. The intervention was cost-effective in reducing depression and disability and improving health-related quality of life and feasible to implement. Conclusion The integrated intervention is feasible and cost-effective even in remote areas and appears ideal for scale-up to other endemic regions in Ethiopia and other countries.